Designing and sciencing: Response to Galle and Kroes. (March 2015) - Farrell, Robert; Hooker, Cliff
Abstract : Galle and Kroes (this journal 2014) have critiqued a recent paper by Farrell and Hooker (this journal 2012) that argued that design and science shared a common core problem-solving (cognitive) process. Contrarily, Galle and Kroes argued for distinct purposive identities to design and science and on that and further grounds argued for their having distinct core cognitive processes. In turn, this paper argues, first, that the distinct purposive identities provided by Galle and Kroes are appropriate, but quite compatible with design and science sharing a common core cognitive process. Second, this paper argues that the further arguments for cognitive distinctness proffered by Galle and Kroes founder on illogicality and/or too shallow an understanding of scientific process. Highlights: It is a common but mistaken belief that design and science are cognitively very different. Strategic analysis of scientific method reveals deep commonalities with design method. Recent criticisms of arguments for cognitive commonality are themselves tellingly flawed. Distinct purposive identities to design and science are compatible with deep cognitive commonality.